Consumer's Choice An Interdisciplinary Approach to Consumer Education. Developed for Grades K-4. - Allegheny Intermediate Unit, Pittsburgh, PA.; Allegheny Intermediate Unit, Pittsburgh, PA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
This manual suggests teaching strategies for integrating consumer education into art, language arts, mathematics, science/health, and social studies in grades K-4. The guide lists consumer education competencies, interdisciplinary structures for consumer education, and provides a chart which relates competencies to page numbers in the guide. Competencies are related to the concepts of the marketplace; legal rights, redress, and consumer law; major purchases of products and services; and special problems such as advertising and product safety. Sections for individual subject areas include the concept, competency, and sub-competency to be covered for each activity, suggested classroom activities, resources, follow-up activities, and performance indicators. In art, students draw a labor saving device, make collages of luxuries they desire and then compute the price, and design packages for new products. Some activities in language arts include interviewing people about their purchasing goals, writing letters of complaint, and consulting a telephone directory to locate agencies which benefit consumers. Mathematics students examine differences between bartering and using money, play monopoly, and prepare a shopping budget. Activities in science and health include presentations by public health officials, discussions of drugs, cigarettes, and alcohol, and examination of advertisements for unnecessary products. Social studies classes examine differences between goods and services, fill out a checklist of basic needs, and comparison shop through newspaper advertisements. Lists of relevant books, film, teaching kits, games, and resources of free material and information are included. (KC)
Availability: Project ICE, Allegheny Intermediate Unit, Suite 1300, Two Allegheny Center, Pittsburgh, Pennsylvania 15202 (free, limited supply).
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
ERIC Note: For related documents, see ED 164 388 and 389.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Civil Rights; Concept Teaching; Consumer Economics; Consumer Education; Daily Living Skills; Educational Strategies; Elementary Education; Integrated Activities; Interdisciplinary Approach; Learning Activities; Purchasing; Social Studies; Teaching Guides; Guides, Classroom -- Teacher